Summer Television Project - Evansville-Vanderburgh School Corp., IN.; Evansville-Vanderburgh School Corp., IN.; Indiana State Dept. of Public Instruction, Indianapolis ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
Three general goals guided the creation of this summer education project: to maintain academic basic skills over the summer months, to involve parents in the learning process, and to involve teachers in reading inservice training. The summer television programs available to all Indiana children are "Ride the Reading Rocket" for grade 2; "Catch a Bubble" for grade 3; "Up, Up and Away" for grades 4-6; "A Math-A-Magical World" for grades 5-8; and "Summer Journal" for grades 7-9. In addition, a series of 10 inservice reading programs for teachers and 1 program for parents of preschoolers have been produced. Included in the project packet are a detailed report of the project, three different brochures describing the television programs for children, suggested motivational strategies for teachers, and information for teachers on the inservice television series. (JM)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Educational level discussed: Early Childhood Education.
Educational level discussed: Elementary Education.
Educational level discussed: Junior High Schools.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Arithmetic; Basic Skills; Early Childhood Education; Educational Programs; Elementary Education; Inservice Teacher Education; Junior High Schools; Mathematics; Parent Participation; Reading; Summer Programs; Television; Elementary Secondary Education Act Title III; Indiana; Reports, Descriptive